Intensified hydrodynamic cavitation using vortex flow based cavitating device for degradation of ciprofloxacin - Patil, Pravin B.; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2022)
The present work, for the first time, establishes degradation behavior of ciprofloxacin (CIP), a widely used fluoroquinolone group of antibiotics, using vortex flow based hydro-dynamic cavitation (HC) for low to high concentrations of CIP (10 and 100 mg/L). Effect of pressure on the degradation of CIP and TOC reduction was investigated on pilot plant scale (capacity 1 m3/h). Process intensifications using aeration as well as hydrogen per-oxide (H2O2) were also investigated. While aeration did not yield any significant en-hancement, process intensification using H2O2 resulted in similar to 200% enhancement in the CIP degradation as compared to HC alone. Excellent degradations, to an extent of 79 & 95%, were achieved corresponding to high cavitational yields of 7.2 x 10-4 mg/J and 86.8 x 10-4 mg/J for CIP concentrations of 10 and 100 mg/L respectively using the process intensified approach of HC and H2O2, not reported so far for cavitating devices without moving ele-ments. The developed methodology demonstrated 4-7 times improvement in per-pass degradation and low cost with high efficiency compared to the conventional cavitation. The results clearly highlight utility of the process intensified approach using H2O2 for the degradation of CIP even at high concentrations, specifically important for pharmaceutical industries requiring zero liquid discharge norms.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Antibiotics removal; ciprofloxacin; Degradation; Oxidation; Wastewater treatment

Improving hydrodynamic cavitation using newer surface-coated cavitation reactors - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
Surface-coated cavitation devices, vortex diode (SCVD) have been reported for the first time for enhancing efficiency of hydrodynamic cavitation (HC). Two surface-coated cavitation reactors using coating of copper and nickel (-50 mu m) were evaluated, also comparing results with conventional reactor vortex diode. The proof of concept is successfully demonstrated for complete degradation of two model organic pollutants, antibioticscephalexin (CFX) and ciprofloxacin (CIP). The surface-coated reactors provide dual activity, and the catalytic effect is highly pronounced with process intensification using H2O2 and/ or pH alternations. Integration of SCVD, pH and H2O2 was the most effective strategy. Complete degradation of the antibiotics was achieved within minutes with H2O2 (-1000 molar ratio) for both Cu and Ni-surface-coated cavitation reactors compared to lower degradation of-19% for CFX and-37% for CIP using only HC. An excellent enhancement of over 300% for CFX degradation at pH 11 and-170% for CIP degradation at pH 4 was obtained. Huge enhancements in per-pass degradation and cavitational yields (up to 400 times) clearly highlight the utility of the surface-coated cavitation reactors in various applications and for cost-effectiveness.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrodynamic cavitation; Oxidation; pollution; Reactor; Technology; Wastewater treatment